IDENTIFIKASI BAKTERI ESHERICHIA COLI DALAM DAGING IKAN TUNA (THUNNUS SP.) DI BALAI KARANTINA IKAN, PENGENDALIAN MUTU DAN KEAMANAN HASIL PERIKANAN (BKIPM) MATARAM: Identification Of Esherichia Coli Bacteria In Tuna Fish (Thunnus sp.) Meat at The Fish Quarantine, Quality Control And Fishery Product Safety Center (BKIPM) Mataram - Adyan Mukhlas; Aminullah Aminullah (Al-Qalbu: Jurnal Pendidikan, Sosial dan Sains, 2026)
This study aims to determine the identification technique of E. coli bacteria in tuna (Thunnus sp.) meat at the Mataram Quarantine, Quality Control and Fishery Product Safety Center (BKIPM). This research method includes laboratory research using participatory methods. Active participation is involvement in an activity carried out directly in the field (Nazir, 2011). Where this method the author follows the activities at BKIPM by observing and interviewing employees and staff, especially BKIPM laboratory technicians who are in charge of E. coli bacteria identification techniques in tuna meat. Data collection techniques consist of observation, interviews, and documentation. The results of this study indicate that the identification of E. coli bacteria in tuna meat carried out at BKIPM starts from sterilization of equipment, sample preparation, presumptive tests using LTB and EC_Broth media, confirmatory tests using L-EMB and PCA media, as well as biochemical tests including indole tests, MR/VP tests, and citrate tests. Based on laboratory test results at the BKIPM (Indonesian Food and Fisheries Agency), samples of baby tuna and filed tuna were declared negative for E. coli, making them safe for consumption.